Synthesis of Bioactive 1,2,3-Triazole-Fused Macrocycles via Azide-Alkyne Cycloaddition - Jahan, Nasrin; Pal, Arkadip; Ansary, Inul (SynOpen, 2024)
A systematic highlight of syntheses reported since 2006 of 1,2,3-triazole-fused macrocycles possessing biological activities such as anticancer, antibacterial, antiviral, anti-inflammatory and antilarval action, is presented in this review. The well-renowned Cu-catalyzed azide-alkyne cycloaddition reaction was noted to be highly efficient and is one the most common methods utilized by scientists for the synthesis of 1,4-disubstituted triazole-fused macrocycles, whereas Ru-catalyzed cycloaddition is common for the formation of 1,5-disubstituted bioactive triazoles. This review would thus be extremely beneficial for both synthetic organic and medicinal chemists.1 Introduction2 Anticancer Derivatives3 Antibacterial Derivatives4 Derivatives with Dual Activity5 Antilarval Derivatives6 Anti-inflammatory Derivatives7 Antiviral Derivatives8 Anti-trypanosomal Derivatives9 Derivatives with Miscellaneous Activities10 Conclusion
Keywords: triazole; macrocycles; anticancer; antibacterial; antiviral; bioactivity